Optical and mass spectra from reactive plasma at magnetron deposition of tantalum oxynitride - Dudin, S.; Yakovin, S.; Zykov, A.; Yefymenko, N. (Вопросы атомной науки и техники, 2021)
Processes in reactive plasma during the magnetron deposition of tantalum oxynitride with ICP activation of reactive gas are studied in dependence on Oxygen fraction. Results of spectroscopic study of optical emission from the plasma and of mass-spectrometry of gas composition in the vacuum chamber in response to ignition of magnetron discharge and inductively coupled plasma are presented. It is shown that dissociation level of all species grows with the magnetron current increase while its dependence on oxygen/nitrogen ratio is non-monotonic. Вивчаються процеси в реактивній плазмі під час магнетронного осадження оксинітриду танталу з ICP-активацією реактивного газу залежно від частки кисню. Представлені результати спектроскопічного дослідження оптичного випромінювання з плазми та мас-спектрометрії газового складу у вакуумній камері у відповідь на запалювання магнетронного розряду та індуктивно зв'язаної плазми. Показано, що рівень дисоціації всіх молекул зростає із збільшенням струму магнетрона, тоді як його залежність від співвідношення кисень/азот є немонотонною. Изучены процессы в реактивной плазме при магнетронном осаждении оксинитрида тантала с ICP-активацией реактивного газа в зависимости от процентного содержания кислорода. Приведены результаты спектроскопических исследований оптического излучения плазмы и масс-спектрометрии состава газа в вакуумной камере при зажигании магнетронного разряда и индуктивно связанной плазмы. Показано, что уровень диссоциации всех молекул растет с увеличением тока магнетрона, а его зависимость от соотношения кислород/азот немонотонна.